Involvement of Aureobasidium pullulans and Rhodotorula glutinis in Russet of d'Anjou Pear Fruit - Spotts, R A; Cervantes, L A (Plant disease, 2002)
d'Anjou pear, the main cultivar grown in the Mid-Columbia Region of Oregon, is subject to russeting of the fruit surface, resulting in reduced quality and value. The role of Aureobasidium pullulans and Rhodotorula glutinis in russet of pear fruit was studied. Inoculations were done at full bloom in 1998 and 1999 and petal fall in 1999 with a log range of concentrations up to 10 CFU/ml. Populations of A. pullulans on floral and fruit tissue were monitored during spring 1999 and 2000 in six orchards with a history of russet. Russet of fruit in both studies was evaluated at harvest. In 1998 neither fungus increased russet. In 1999, inoculation with two strains of each fungus at 10 CFU/ml increased russet. Inoculation with 10 or 10 CFU/ml did not increase russet in either year. In commercial orchards, there was no correlation between fruit russet and the populations of A. pullulans on floral and fruit tissue. Populations were less than 10 CFU/g of tissue. We conclude that A. pullulans and R. glutinis are not major contributors to russet of d'Anjou pear fruit in the Mid-Columbia Region.